{Picolinamide residue-based hydrogen-selective ISEs for the potentiometric measurement of subzero pH values} - Fouskaki, Maria; Gimisis, Thanasis; Chaniotakis, Nikolas A. (Electroanalysis, 2002)
The development of new hydrogen selective neutral carriers based on 3-hydroxypicolinic acid derivatives, and its application to pH selective liquid membrane ISE based on these compounds is described. The optimization of the sensor has been based on the use of different plasticizers, additives, and mole ratios of the picolinate derivatives. Based on these results it is shown that the membrane composition can be adjusted for the measurement of pH at very low pH values (down to pH -0.5) and up to at least pH 10. The ability of the presented carriers to measure hydrogen activities up to 3N gives new directions in the use of these sensors for a variety of critical applications.
Keywords: PH selective; [3-Hydroxypicolinic acid derivatives